1937
DOI: 10.1111/j.1746-1561.1937.tb01692.x
|View full text |Cite
|
Sign up to set email alerts
|

The Nurse in the School Health Service*

Abstract: veryone knows how and why school nursing was begun E in the United States. From a relatively simple program Ldce Michi-Building, Chicago, 111. pecksgc of Kleenex l a claumom uv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Also in the literature it can be observed that school-based health services and school nursing services are service rendering types that provide positive contribution to students’ health and academic results. 4,6,10,11,17,26,27,33-35 …”
Section: Discussionmentioning
confidence: 99%
“…Also in the literature it can be observed that school-based health services and school nursing services are service rendering types that provide positive contribution to students’ health and academic results. 4,6,10,11,17,26,27,33-35 …”
Section: Discussionmentioning
confidence: 99%
“…The first round of analysis resulted in a master-list of codes. I continued to review the data for findings that were repeated among participants interviewed in the study using constant-comparison analysis (Glaser & Strauss, 1967 Bigby, 2004;Grant, 2001;Macdonough, 2001;Percy, 2006). The function of the school nurse has varied since its origin and the variations in the school nurse's role have resulted from a combination of societal changes.…”
Section: Discussionmentioning
confidence: 99%